SYSTEMATIZATION, DISTRIBUTION, AND TERRITORIES OF THE MIDDLE CEREBRAL ARTERY ON THE SURFACE OF THE BRAIN IN NUTRIA (MYOCASTOR COYPUS) - Goltz, Laura Ver; Chiarello, Guilherme Pereira; Voll, Juliana; de Araújo, Ana Cristina Pacheco; Campos, Rui (Seven Editora, 2025)
The nutria (Myocastor coypus) is a semi-aquatic rodent, valued in the fur and meat industry. The aim of this study is to describe and systematize the middle cerebral artery on the surface of the brain in nutria, establishing a standard model and its main variations and territories in this species. The 30 animals were euthanized, the arterial system was washed and filled with colored latex and fixed in formaldehyde. Schematic drawings were made to elaborate the results. The brain was vascularized exclusively by the vertebrobasilar system. The terminal branches of the basilar artery gave rise to the rostral cerebellar, caudal cerebral, rostral choroidal, and middle cerebral arteries, and its terminal branch, the rostral cerebral artery. The middle cerebral artery was the last collateral branch emitted by the basilar artery, projecting laterally through the lateral fossa of the brain, giving off branches to the paleopallium of the region. Upon crossing the lateral rhinal sulcus, it formed one or two main axes that ascended to the convex surface of the cerebral hemisphere, giving off caudal and rostral convex hemispheric branches. In its initial course, within the lateral fossa of the brain, the middle cerebral artery emitted caudal and rostral central branches. The middle cerebral artery emitted convex hemispherical branches caudal and rostral to the convex surface of the cerebral hemisphere. The middle cerebral artery was the last collateral branch of the basilar artery as it passed through the optic tract, as in capybaras, ground squirrels, and chinchillas. The projection of the middle cerebral artery differed among rodent species, but its branching and territory were similar between nutria and chinchillas.DOI: https://doi.org/10.56238/sevened2025.037-050